Development and evaluation of a digital dental modeling method based on grating projection and reverse engineering software - Zhou, Qin; Wang, Zhenzhen; Chen, Jun; Song, Jun; Chen, Lu; Lu, Yi (The Journal of prosthetic dentistry, 2016)
For reasons of convenience and economy, attempts have been made to transform traditional dental gypsum casts into 3-dimensional (3D) digital casts. Different scanning devices have been developed to generate digital casts; however, each has its own limitations and disadvantages. The purpose of this study was to develop an advanced method for the 3D reproduction of dental casts by using a high-speed grating projection system and noncontact reverse engineering (RE) software and to evaluate the accuracy of the method. The methods consisted of 3 main steps: the scanning and acquisition of 3D dental cast data with a high-resolution grating projection system, the reconstruction and measurement of digital casts with RE software, and the evaluation of the accuracy of this method using 20 dental gypsum casts. The common anatomic landmarks were measured directly on the gypsum casts with a Vernier caliper and on the 3D digital casts with the Geomagic software measurement tool. Data were statistically assessed with the t test. The grating projection system had a rapid scanning speed, and smooth 3D dental casts were obtained. The mean differences between the gypsum and 3D measurements were approximately 0.05 mm, and no statistically significant differences were found between the 2 methods (P>.05), except for the measurements of the incisor tooth width and maxillary arch length. A method for the 3D reconstruction of dental casts was developed by using a grating projection system and RE software. The accuracy of the casts generated using the grating projection system was comparable with that of the gypsum casts.